EUDRAGIT COATED ALGINATE BEADS BEARING OXALIPLATIN LOADED LIPOSOMES: FORMULATION, OPTIMIZATION AND IN VITRO CHARACTERIZATION - TIWARI, ANKITA; JAIN, SANJAY K. (International Journal of Applied Pharmaceutics, 2021)
Objective: The present investigation aimed to develop and characterize Eudragit S-100 coated alginate beads bearing oxaliplatin loaded liposomes for colon-specific drug delivery. Methods: Liposomes were formulated by the thin-film hydration method. The process and formulation variables were optimized by Box-Behnken design (BBD) with the help of Design-Expert® Software. Three independent variables taken were HSPC: Chol molar ratio (X1), hydration time (X2), and sonication time (X3). The response variables selected were entrapment efficiency of oxaliplatin, polydispersity index, and vesicle size. Results: The liposomes possessed an average vesicle size of 110.1±2.8 nm, PDI 0.096±0.3, zeta potential of-6.70±1.4 mV, and entrapment efficiency of 27.65%. The beads were characterized for their size, in vitro drug release, and swelling index. The degree of swelling of the beads was found to be 2.3 fold higher at pH 7.4 than at pH 1.2. The in vitro drug release depicted a sustained drug release in 48 h. Conclusion: The outcomes of the study proposed that the developed system can be effectively used for site-specific drug delivery to the colon via the oral route.